Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

La fabrique moléculaire du genre : hormones sexuelles, industrie et médecine avant la pilule - Gaudillière, Jean-Paul (Cahiers du Genre, 2003)
L’histoire des hormones sexuelles est le plus souvent discutée en référence à l’invention de la pilule dans les années d’après-guerre. La molécularisation des sexes a toutefois été beaucoup plus précoce, plus complexe et plus contradictoire que cette vision ne le laisse penser. Parce qu’elle a fait intervenir tout à la fois une recherche biomédicale de haut niveau, une industrie pharmaceutique puissante et la biopolitique du régime nazi, la configuration allemande offre un terrain privilégié pour interroger les dynamiques de cette fabrique moléculaire du genre. Centré sur les rapports entre biologistes, industriels producteurs d’hormones et médecins spécialistes de la reproduction, cet article aborde trois aspects différents de l’histoire des stéroïdes sexuels avant la pilule : l’idée d’un continuum des sexes biologiques et les discussions qu’elle a suscitées, la médicalisation de la stérilité féminine et de la ménopause, et les multiples usages de la testostérone.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; féminisme radical; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques